The human corpse as aesthetic-therapeutic. (2nd January 2023) - Mathijssen, Brenda
ABSTRACT: This paper shows how the human corpse can function as an aesthetic-therapeutic for the deceased, the bereaved and for death care professionals. It understands the human corpse as a liminal entity that is characterised by a specific materiality, biography and self-referentiality. Because of these attributes the corpse can be employed as an aesthetic-therapeutic by the bereaved and by death care professionals in response to a death. On the basis of participant observation in the death care industry and qualitative interviews with bereaved people and funeral professionals in the Netherlands, the paper discusses four engagements with the dead body in the period prior to the funeral: i) caring, ii) sustaining, iii) restoring, and iv) disregarding the dead body. Crucially, it shows how such engagements can contribute to the well-being of those involved, including the deceased, who is often understood to be sentient. Furthermore, by focusing on cases where the corpse is disregarded, the paper argues that an aesthetic-therapeutic understanding of the human corpse is hegemonic in the death care industry. The analysis and conclusion offer insights to scholars in the interdisciplinary field of death studies, as well as reflections for practitioners in end-of-life and death care.